2010
DOI: 10.1007/s00300-010-0841-9
|View full text |Cite
|
Sign up to set email alerts
|

Variability of protistan and bacterial communities in two Arctic fjords (Spitsbergen)

Abstract: Krossfjorden and Kongsfjorden are Arctic fjords on the western side of Spitsbergen. These fjords share a common mouth to the open sea, and both are inXuenced by the input of sediment-rich glacial meltwater leading to decreased surface salinity, increased turbidity and decreased light penetration during summer. Earlier classical taxonomic studies had described the pelagic protistan composition of the Kongsfjorden during summer, revealing the dominance of Xagellates of often unresolved taxonomic origin. Only lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
50
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 58 publications
10
50
0
Order By: Relevance
“…Therefore, caution has to be taken when judging the general validity of our results for the response of the bacterial community to ocean acidification in Arctic waters. In addition, the bacterial community structure in Kongsfjorden can vary considerably seasonally (Piquet et al, 2010). Nevertheless, the fact that other mesocosm studies in a Norwegian fjord found similar results suggests an emerging pattern of secondary effects on PA bacteria under ocean acidification, while FL bacteria stay rather unchanged.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Therefore, caution has to be taken when judging the general validity of our results for the response of the bacterial community to ocean acidification in Arctic waters. In addition, the bacterial community structure in Kongsfjorden can vary considerably seasonally (Piquet et al, 2010). Nevertheless, the fact that other mesocosm studies in a Norwegian fjord found similar results suggests an emerging pattern of secondary effects on PA bacteria under ocean acidification, while FL bacteria stay rather unchanged.…”
Section: Discussionmentioning
confidence: 77%
“…the runoff of melt water. While the bacterial community was found to be spatially relatively homogenous in Kongsfjorden (Zeng et al, 2009), it was shown to differ significantly from that of a neighbouring fjord with less water exchange (Piquet et al, 2010), indicating spatial variability on a larger scale. A high spatial variability is also present in the factors limiting bacterial growth in the coastal waters of Svalbard (Vadstein, 2011), and this has been proposed to influence the reaction of the bacterial community to CO 2 perturbation .…”
Section: Discussionmentioning
confidence: 80%
“…Interestingly, we observed that the relative abundance of Betaproteobacteria in surface water samples decreased as a function of distance either from the coast or from the pack ice. A number of large glacial fjords flow into the Western coastal waters off Svalbard (Figure 1) and the Betaproteobacteria have been retrieved from Kongsfjorden there (Zeng et al, 2009(Zeng et al, , 2013Piquet et al, 2010). The group have also been seen to predominate in Arctic pack ice summer melt pools (Brinkmeyer et al, 2004), which might further seed ocean waters upon thawing.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria in the sediments directly impact nutrient and carbon cycles, as they complete the Wnal decomposition step by breaking down organic carbon and making it available for other organisms (Fenchel and Jørgensen 1977;Falkowski et al 2008;Robador et al 2009). However, little information is available about the bacterial community in Spitsbergen fjords (Jankowska et al 2005;Jiang et al 2005;Zeng et al 2009;Piquet et al 2010); thus, the relationship between bacterial activity and organic matter in Hornsund requires further study.…”
Section: Comparison Of Meiofauna Between Hornsund and Kongsfjordenmentioning
confidence: 99%